2015
DOI: 10.1002/ajmg.b.32376
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of heroin relapse: Personality traits, impulsivity, COMT gene Val158met polymorphism in a 5‐year prospective study in Shanghai, China

Abstract: Relapse is a typical feature of heroin addiction and rooted in genetic and psychological determinants. The aim of this study was to evaluate the effect of personality traits, impulsivity, and COMT gene polymorphism (rs4680) on relapse to heroin use during 5-year follow up. 564 heroin dependent patients were enrolled in compulsory drug rehabilitation center. 12 months prior to their release, personality traits were measured by BIS-11 (Barratt Impulsiveness Scale-11) and Temperament and Character Inventory (TCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
5
8
0
Order By: Relevance
“…An alternate hypothesis is that the mood and personality differences associated with COMT genotype may simply make Met/Met patients more amenable to treatment in general. This latter explanation would fit with data from a recently published longitudinal study of Chinese opioid dependent patients (42). Patients who were not receiving methadone were enrolled in the study after undergoing mandatory detoxification and followed for five years.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An alternate hypothesis is that the mood and personality differences associated with COMT genotype may simply make Met/Met patients more amenable to treatment in general. This latter explanation would fit with data from a recently published longitudinal study of Chinese opioid dependent patients (42). Patients who were not receiving methadone were enrolled in the study after undergoing mandatory detoxification and followed for five years.…”
Section: Discussionsupporting
confidence: 77%
“…Patients who were not receiving methadone were enrolled in the study after undergoing mandatory detoxification and followed for five years. Patients carrying the Met allele were more likely than Val/Val individuals to be receiving methadone maintenance therapy and to be abstinent from heroin at the five year time point (42). Since no clear association between Val158Met genotype and susceptibility to opioid dependence has been established, these findings may indicate that the polymorphism affects the maintenance phase of opioid dependence but not necessarily initiation of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also in the HC group, this association was limited to male subjects, suggesting a gene x sex effect in the determination of NS levels. More in detail, we found that the Val/Val genotype was associated with higher NS levels in this subgroup of subjects, partially consistent with literature data about the effects of this genotype on impulsivity and addictive behaviors [64, 65], which are both associated with NS dimensions [66, 67]. Furthermore, the lack of association observed in BD sample may support the hypothesis that BD pathophysiological process alters the neurobiological substrates of NS, as previously stated.…”
Section: Discussionsupporting
confidence: 91%
“…This was done partly due to the fact that the sample size in our study was relatively low and hence certain groups would consist of less than 10 participants. However, the grouping strategy used in our study is not an uncommon one 39,6264 , and a number of studies did not find impulsivity differences between Val/Met and Met/Met individuals, enabling us to assign them into one group 48,49 (but see: 50 ). Yet, to alleviate the concern that such grouping strategy might have affected our results, we performed additional analysis while grouping participants into three groups based on the COMT SNP.…”
Section: Discussionmentioning
confidence: 97%
“…While the latter practice is commonly used among studies 39,41 , we did not find studies who grouped participants into Met carriers and non-carriers. However, a number of studies investigating impulsivity did not find differences between Val/Met and Met/Met individuals, enabling us to assign them into one group ( 48,49 but see: 50 ). Additionally, we post-hoc analysed the data with three separate groups for the COMT SNP – heterozygotes and homozygotes.…”
Section: Methodsmentioning
confidence: 99%